2017
DOI: 10.1142/s0219649217500186
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Students’ Satisfaction Factors in E-Learning Environment: A Case Study on Saudi Arabian University

Abstract: Despite the proliferation of studies outlining the immense benefits obtained from e-learning, the understanding of students’ satisfaction with e-learning in developing countries is still unclear. Therefore, this paper investigates the relationship between Saudi students’ satisfaction with online courses and a number of individual, as well as institutional characteristics cited as robust predictors of students’ satisfaction in the educational literature. These include: students’ levels of internet self-efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…First, all the research articles selected for deep analysis were listed against e-learning user relationships and HCI. These two factors were separately subdivided into different categories as per the studies by Abdel (2017), Cigdem and Ozturk (2016), Goh et al (2017), Lee and Lee (2015) and Paechter et al (2010). SSI, SII and SCI were taken as the types of e-learning user relationships, while usability and user satisfaction were taken as the categories of HCI.…”
Section: Jsit 213mentioning
confidence: 99%
“…First, all the research articles selected for deep analysis were listed against e-learning user relationships and HCI. These two factors were separately subdivided into different categories as per the studies by Abdel (2017), Cigdem and Ozturk (2016), Goh et al (2017), Lee and Lee (2015) and Paechter et al (2010). SSI, SII and SCI were taken as the types of e-learning user relationships, while usability and user satisfaction were taken as the categories of HCI.…”
Section: Jsit 213mentioning
confidence: 99%
“…Khurshid [104] found that charismatic, participatory, and democratic teaching styles yield more engaged students in a study at Jazan University. Abdel-Jaber [112] analyzed the covariates of students' satisfaction at the Arab Open University in Eastern Saudi Arabia and found that instructor's interactivity is the single most predictor of students' enjoyment and participation in virtual courses. Alsamani and Daif-Allah [113] suggested that group-based projects generate better students' interest and performance in computer science courses taught in English at Al-Qassim University in central Saudi Arabia.…”
Section: Faculty Engagement In Saudi Higher Educationmentioning
confidence: 99%